2006
DOI: 10.1590/s1678-77572006000100006
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal photographic observation of the occurrence of bubbles in pit and fissure sealants

Abstract: The purpose of this study was to employ photographic evaluation to observe the presence or absence of bubbles in pit and fissure sealants Concise and Prisma Shield, at 7 days, 18 months, 36 months and 11 years after accomplishment of treatment.Methods:A hematoxylin-based staining solution was applied to the occlusal surface at the study periods, which allowed assessment of the sealing material on the surface. All occlusal surfaces were photographed and the photographs corresponding to each period were subjecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
2
4
0
2
Order By: Relevance
“…In the present study, it was observed, through statistical analysis, that there was no significant difference between these materials used as sealants, in agreement with the results found by other authors 24,26 . Regarding the composition of the resinous sealants used in the research, it is possible to observe similarity between the materials, which may be the reason for not having statistical differences between the sealants in the researched criteria.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, it was observed, through statistical analysis, that there was no significant difference between these materials used as sealants, in agreement with the results found by other authors 24,26 . Regarding the composition of the resinous sealants used in the research, it is possible to observe similarity between the materials, which may be the reason for not having statistical differences between the sealants in the researched criteria.…”
Section: Discussionsupporting
confidence: 93%
“…In a longitudinal evaluation of sealants after 10 years of application, it was verified that the failure is related to some factors: fluoride use, caries experience, operative technique, child behavior, tooth type and age 23 . The application of resinous sealants may appear as bubbles, however, in a longitudinal evaluation of 11 years, it was verified that these bubbles dissolve over time 24 .…”
Section: Discussionmentioning
confidence: 95%
“…s a l i v a . 1 There' was' no' signi8icant' difference' between' abrasives' agents' (p' =' 0.5847).' Means' followed' by' different' letters' (uppercase' in' horizontal' and'…”
mentioning
confidence: 98%
“…Dentre as medidas preventivas e que apresenta eficácia comprovada, podemos destacar os selantes de fóssulas e fissuras, muito utilizados na Odontologia Preventiva mundial 1,2 . O selamento da superfície oclusal elimina as regiões propícias ao acúmulo de bactérias e restos alimentares, difíceis de serem removidos pela escovação habitual, impedindo o início do processo carioso 3 .…”
Section: Introductionunclassified